Direct use of peak ground motion parameters for the estimation of inelastic displacement ratio of SDOF systems subjected to repeated far fault ground motions - Durucan, Cengizhan; Gumus, Muhammed (Springer, 2018)
This study is aimed at developing statistical equations to estimate the inelastic displacement ratio of singledegree- of-freedom systems subjected to far fault repeated earthquakes. In the study, peak ground motion parameters are used to define the scatter of the original data. The ratio of peak ground acceleration to peak ground velocity, and peak ground velocity of the ground motion records and structural parameters such as period of vibration and lateral strength ratio are used in the proposed equations. For the development of the equations, nonlinear time history analyses of single-degree-offreedom systems are conducted. Then, the results are used in a multivariate regression procedure. The equations are verified by comparing the estimated results with the calculated results. The average error and coefficient of variation of the proposed equations are presented. The analyses results revealed that the direct use of peak ground motion parameters for the estimation of inelastic displacement ratio significantly reduced the scatter in the original data and yielded accurate results. From the comparative results it is also observed that results obtained using equations specific to peak ground velocity or peak ground acceleration to peak ground velocity ratio are similar.
Keywords: C1; peak ground velocity; peak ground acceleration; far fault ground motions; sequential ground motions